2004
DOI: 10.1038/sj.npp.1300484
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of G Protein-Activated Inwardly Rectifying K+ Channels by Various Antidepressant Drugs

Abstract: G protein-activated inwardly rectifying K þ channels (GIRK, also known as Kir3) are activated by various G protein-coupled receptors. GIRK channels play an important role in the inhibitory regulation of neuronal excitability in most brain regions and the heart rate. Modulation of GIRK channel activity may affect many brain functions. Here, we report the inhibitory effects of various antidepressants: imipramine, desipramine, amitriptyline, nortriptyline, clomipramine, maprotiline, and citalopram, on GIRK channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 74 publications
(84 reference statements)
4
65
0
Order By: Relevance
“…Kir channels allow K + ions to enter the cells much more readily than does K + permeation in the outward direction (Kubo et al, 1993a). In the hK solution used to readily analyze Kir currents by enhancing the magnitude of currents, the K + equilibrium potential (E K ) was close to 0 mV, and inward K + current flow through GIRK channels was observed at negative holding potentials, as shown in previous studies (Dascal et al, 1993;Lewohl et al, 1999;Kobayashi et al, 2004b). For examining the effect of intracellular ifenprodil, 23 nl of 10 mM ifenprodil or 30 mM lidocaine N-ethyl bromide (QX-314) dissolved in distilled water was administered to an oocyte through an additional pipette by pressure injection using a Nanoliter injector (World Precision Instruments, Sarasota, FL, USA) as described previously , and the oocyte currents were then continuously recorded for approximately 30-40 min.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…Kir channels allow K + ions to enter the cells much more readily than does K + permeation in the outward direction (Kubo et al, 1993a). In the hK solution used to readily analyze Kir currents by enhancing the magnitude of currents, the K + equilibrium potential (E K ) was close to 0 mV, and inward K + current flow through GIRK channels was observed at negative holding potentials, as shown in previous studies (Dascal et al, 1993;Lewohl et al, 1999;Kobayashi et al, 2004b). For examining the effect of intracellular ifenprodil, 23 nl of 10 mM ifenprodil or 30 mM lidocaine N-ethyl bromide (QX-314) dissolved in distilled water was administered to an oocyte through an additional pipette by pressure injection using a Nanoliter injector (World Precision Instruments, Sarasota, FL, USA) as described previously , and the oocyte currents were then continuously recorded for approximately 30-40 min.…”
mentioning
confidence: 51%
“…The current responses were abolished in the presence of 3 mM Ba 2 + , which blocks the Kir channel family including GIRK channels (n ¼ 3). The 3 mM Ba 2 + -sensitive current components in oocytes expressing GIRK channels are considered to correspond to the magnitudes of GIRK1/2 currents (Kobayashi et al, 2004b). In uninjected oocytes, ifenprodil, even at the highest concentration used, or 3 mM Ba 2 + caused no significant response ( Figure 1c; n ¼ 4), suggesting no effect of ifenprodil or Ba 2 + on intrinsic oocyte channels.…”
Section: Inhibition Of Girk Channels By Ifenprodilmentioning
confidence: 99%
“…Thus, alcoholinduced changes in affinity of GIRK for PIP 2 may recapitulate some of the same events induced by Gβγ binding. The cross-talk between alcohol, Gβγ, and the low affinity for PIP 2 suggest that GIRK channels have evolved to be sensitive to small molecules that either inhibit (48,49) or activate (3-5) the channel.…”
Section: Discussionmentioning
confidence: 99%
“…The ligand-gated potassium channels are members of a family of inward-rectifier potassium channels and are GIRK channels which are gated directly by GTP-binding protein βγ-subunit [11,28]. It was already reported that some psychotropic drugs with higher concentration ranges inhibited a cardiac type of GIRK channel in an over-expression system of Xenopus oocytes and CHO cells [16,17,28]. Moreover, it was reported that chlorpromazine inhibited the acetylcholine-induced I K.ACh with a threshold of ~30 nM in rat atrial cardiomyocyte [1].…”
Section: Discussionmentioning
confidence: 99%
“…Our group previously reported that benzodiazepines, antianxiety drugs, inhibited the acetylcholine receptor-operated potassium current (I K.ACh ) in relatively higher concentration than that of clinical concentration [26]. It was reported that a couple of antipsychotics and antidepressants inhibited GIRK channel current in an over-expression system [16,17]. Moreover, chlorpromazine inhibited I K.ACh in rat cardiac myocytes [1].…”
mentioning
confidence: 99%